1993
DOI: 10.1007/bf00399090
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fish oil augments nitric oxide production or release in patients with Type 2 (non-insulin-dependent) diabetes mellitus

Abstract: Decreased release of nitric oxide from damaged endothelium is responsible for the impaired endothelium-dependent vasodilator responses found in animal models of vascular disease. Dietary supplementation with fish oils has been shown to augment endothelium-dependent relaxations, principally by improving the release of nitric oxide from injured endothelium. Using forearm venous occlusion plethysmography we studied vascular responses to 60, 120, 180 and 240 nmol/min of acetylcholine (an endothelium-dependent vaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
2

Year Published

1994
1994
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(100 citation statements)
references
References 29 publications
(26 reference statements)
4
93
2
Order By: Relevance
“…The trials included in the pooled analyses were small, with a median of 23 patients. Seventeen of the published papers were duplicate publications of six trials [22, 27, 33, 34, 36-38, 40, 42-46, 48, 51, 54, 55]; multiple papers for each trial are indicated by the following grouping of references: [22,38], [27,34,36,37], [40,54,55], [42,48,51], [43,46], [44,45]. There was sufficient information on only 12 of the 98 outcomes to allow data to be pooled, the results of which are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The trials included in the pooled analyses were small, with a median of 23 patients. Seventeen of the published papers were duplicate publications of six trials [22, 27, 33, 34, 36-38, 40, 42-46, 48, 51, 54, 55]; multiple papers for each trial are indicated by the following grouping of references: [22,38], [27,34,36,37], [40,54,55], [42,48,51], [43,46], [44,45]. There was sufficient information on only 12 of the 98 outcomes to allow data to be pooled, the results of which are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…LCPUFAs not only enhance the formation of the beneficial PGs but also inhibit ACE activity (Kumar & Das, 1997;Das, 1997;Das, 2001a) and augment the synthesis of eNO (McVeigh et al, 1993). On the other hand, there is evidence to suggest that the L-arginine-NO system could upregulate the metabolism of LCPUFAs in experimental animals (Mohan & Das, 2000.…”
Section: Lcpufas As Endogenous Antihypertensive Agentsmentioning
confidence: 99%
“…[18][19][20][21] Dihomo-GLA, AA, EPA and DHA not only form precursors to vasodilator and platelet anti-aggregator factors PGE 1 , PGI 2 and PGI 3 , but also inhibit ACE activity and augment the synthesis of endothelial NO. [22][23][24][25] Therefore, PUFA deficiency leads to increased ACE activity, which causes an increase in the levels of angiotensin II that, in turn, augment superoxide anion generation by activating NADPH oxidase, events that lead to a decrease in NO levels. 26 As the brain contains all components of the renin-angiotensin system, it is likely that low brain levels of DHA and EPA could enhance the level of angiotensin II, increasing the generation of free radicals and thereby accelerating the development of hypertension.…”
mentioning
confidence: 99%